Marzanoptera tersillae, a new balaenopterid genus and species from the Pliocene of Piedmont, north-west Italy. Issue 4 (24th November 2020) - Bisconti, Michelangelo; Damarco, Piero; Pavia, Marco; Sorce, Barbara; Carnevale, Giorgio
Abstract: Marzanoptera tersillae gen. & sp. nov., a new balaenopterid from the Pliocene of the Piedmont in north-west Italy, is described based on a partial skeleton and compared with other living and fossil baleen whales. Marzanoptera tersillae shares characters, such as the shape of the supraoccipital, glenoid fossa of the squamosal and zygomatic process of the squamosal, with ' Balaenoptera ' bertae . We used a computed tomography scan to view parts of the skull that were otherwise impossible to observe, such as the periotic. A phylogenetic analysis based on 355 character states scored from 87 taxa revealed a well-resolved hypothesis of relationships for Balaenopteridae and a general phylogenetic hypothesis for chaeomysticetes. The monophyly of all superfamily- and family-rank clades and of crown balaenopterid species was confirmed. In addition, a monophyletic group including most basal thalassotherian taxa was recovered. The mollusc fauna associated with the specimen was autochtonous and constituted a residual fossil assemblage indicative of an environmental context located below the base of the storm wave, characterized by a low-energy hydrodynamic regimen. Many shark teeth have been found in close association or embedded within the bones, suggesting a possible scavenging action by two shark species on the whale carcass.